Tanggung Jawab PT. Alfariya Trijaya Tbk (Alfamart) Terhadap Uang Kembalian Konsumen Ditinjau Dari Undang-Undang Nomor 8 tAHUN 1999 Tentang Perlindungan Konsumen - Fadia, Nisa; Jafar, Sofyan; Kurniasari, Tri Widya (Fakultas Hukum Universitas Malikussaleh, 2024)
The practice of diverting change under the pretext of donation ia often carried out by several retail traders in Indonesia PT. Sumber Alfariya Trijaya Tbk regarding the transfer of consumer money back info donations base on Law Number 8 of 1999 concerning Consumer Protection.This study aims to determine Alfamart's responsibility for the use of consumer change diverted to donations in terms of Law Number 8 Year 1999 concerning Consumer Protection and to determine the legal consequences for Alfamart if there is a violation in the process of using consumer change diverted to donations.This research uses qualitative research methods and empirical juridical approaches. The results of the research show that PT SAT's responsibility to the community who agreed to donate the money from the transaction is to give all the donations collected to the recipient foundations and ensure that the donations are actually used so that they are beneficial to those in need. The legal consequences are that business actors who violate the provisions of the GCPL are punished with a maximum imprisonment of 5 (five) years or a maximum fine of Rp 2,000,000,000.00 (two billion rupiah)It is suggested that PT SAT is expected to be responsible for the collection and distribution of donations to the recipient foundation. Alfamart business actors should provide direction to cashier officers who deal directly with consumers in buying and selling transactions to explain in advance about the distribution of donation funds clearly so that consumers know that the money they donate is not misused.